KORELASI SELF CONFIDENCE (KEPERCAYAAN DIRI) DENGAN MOTIVASI BELAJAR PESERTA DIDIK KELAS IV SDN GUGUS I KECAMATAN BOLO KABUPATEN BIMA TAHUN PELAJARAN 2021/2022 - Rahman, Arif; Darmiany, Darmiany; Husniati, Husniati (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The purpose of this study was to determine the correlation between self-confidence and learning motivation of elementary school students in cluster I, Bolo District, Bima Regency. This research uses a quantitative approach with a correlational method. The population in this study were all the fourth grade students of SDN Cluster I, Bolo District, Bima Regency as many as 90 students. This study uses a probability sampling technique by taking samples by random sampling, so that a sample of students is obtained. The data collection method in this study is to use product moment with the person assisted by SPSS version 2021. So the results of data analysis show that the r value is 22.92% with the test criteria that Ha is accepted and H0 is rejected. So it can be said that there is a clarification of self-confidence with student learning motivation in cluster I, Bolo District, Bima Regency